Interventions for dysphagia in acute stroke (Review) - Bath, Philip M.W.; Bath-Hextall, F.J.; Smithard, D.G. (Wiley Publishers, 2008)
Background It is unclear how dysphagic patients should be fed and treated after acute stroke. Objectives The objective of this review was to assess the effect of different management strategies for dysphagic stroke patients, in particular how and when to feed, whether to supplement nutritional intake, and how and whether to treat dysphagia. Search strategy We searched the Cochrane Stroke Group trials register, Medline, Embase, ISI, and existing review articles.We contacted researchers in the field and equipment manufacturers. Date of the most recent searches: March 1999. Selection criteria Unconfounded truly or quasi randomised controlled trials in dysphagic patients with acute/subacute (within 3 months) stroke. Data collection and analysis Three reviewers independently applied the trial inclusion criteria. Two reviewers assessed trial quality and extracted the data. Main results Percutaneous endoscopic gastrostomy (PEG) versus nasogastric tube (NGT) feeding: two trials (49 patients) suggest that PEG reduces end-of-trial case fatality (Peto Odds Ratio, OR 0.28, 95% CI 0.09 to 0.89) and treatment failures (OR 0.10, 95% CI 0.02 to 0.52), and improves nutritional status, assessed as weight (Weighted Men Difference, WMD +4.1 kg, 95% CI -4.3 to +12.5), mid-arm circumference (WMD +2.2 cm, 95% CI -0.5 to +4.9) or serum albumin (WMD + 7.0 g/l, 95% CI +4.9 to +9.1) as compared with NGT feeding; two larger studies are ongoing. Timing of feeding: no completed trials; one large study is ongoing. Swallowing therapy for dysphagia: two trials (85 patients) suggest that formal swallowing therapy does not significantly reduce end-of-trial dysphagia rates (OR 0.55, 95%CI 0.18 to 1.66). Drug therapy for dysphagia: one trial (17 patients); nifedipine did not alter end-of-trial case fatality or the frequency of dysphagia. Nutritional supplementation: one trial (42 patients) found a non-significant trend to a lower case fatality, and significantly increased energy and protein intake; one large trial is ongoing and data is awaited from two other studies. Fluid supplementation: one trial (20 patients) found that supplementation did not alter the time to resolution of dysphagia. Authors’ conclusions Too few studies have been performed, and these have involved too few patients. PEG feeding may improve outcome and nutrition as compared with NGT feeding. Further research is required to assess how and when patients are fed, and the effect of swallowing or drug therapy on dysphagia.